A missing element in the empirical post Keynesian theory of inflation—total credits to households: A first-differenced VAR approach to U.S. inflation. Issue 4 (1st October 2020) - Kim, Hongkil
Abstract: This paper analyzes U.S. inflation since the early 1980s, using the post Keynesian theory of inflation. Our empirical model that contains both supply- and demand-side variables is run over the total sample and the recent subsample after we notice a structural break in 2000Q3. The empirical results of the generalized impulse response analysis based on the estimated vector autoregression suggests that supply-side variables are significant in explaining U.S. inflation regardless of time, whereas the demand-side variable, the excess credit creation/depletion of households, is only crucial in the recent period. It demonstrates a missing element in the empirical post Keynesian theory of inflation. Furthermore, it is found that current monetary policy tools of maneuvering target interest rates and controlling monetary supply is not effective to their policy goals toward price stability.